Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 1902 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "TaxonKey is Crataegus mexicana Moc. & Sessé ex DC.", "TaxonKey is Alchemilla vulcanica Zoll. & Moritzi", "TaxonKey is Fragaria vesca Pursh", "TaxonKey is Rosaceae", "TaxonKey is Lachemilla velutina (S.Watson) Rydb.", "TaxonKey is Alchemilla velutina S.Watson", "TaxonKey is Amelanchier denticulata (Kunth) K.Koch, 1869", "TaxonKey is Lachemilla vulcanica (Cham. & Schltdl.) Rydb.", "TaxonKey is Acaena elongata L.", "TaxonKey is Alchemilla aphanoides Mutis ex L.f.", "TaxonKey is Holodiscus pachydiscus (Rydb.) Standl.", "TaxonKey is Lindleya mespiloides Schltdl.", "TaxonKey is Alchemilla procumbens Rose", "TaxonKey is Holodiscus fissus (Lindl.) C.K.Schneid.", "TaxonKey is Cercocarpus fothergilloides Kunth", "TaxonKey is Alchemilla sibbaldiifolia Kunth", "TaxonKey is Alchemilla aphanoides var. subalpestris (Rose) L.M.Perry", "TaxonKey is Duchesnea indica (Andr.) Focke", "TaxonKey is Agrimonia pringlei Rydb.", "TaxonKey is Alchemilla pectinata Kunth", "TaxonKey is Rubus L." ] }, "Country is Mexico", "HasCoordinate is true", "BasisOfRecord is Specimen" ] } The dataset includes 1902 records from 28 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000396-160822134323880/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences